Advances in the treatment of chemical waste generated by the Federal University of Itajubá (UNIFEI) and possible mitigation measures (Research, Society and Development, 2020)
The objective of this work was to inventory the treatment of chemical waste generated in the laboratories of UNIFEI-Itajubá in view of the final destination given to them. The methodology used in the study was verification through questionnaires, aiming to obtain information on the frequency of practices; the chemicals used; the volume of waste generated; the time and form of storage and the final disposal forms of these. A wide range of chemical substances have been used, with their waste disposed of properly, often being recycled after use in practical classes. According to the results obtained, it was found that UNIFEI laboratory waste management has evolved since the beginning of this work in 2008, mainly after the creation of new undergraduate courses. The hiring of chemistry technicians to work in the newly built laboratories was of paramount importance with regard to the management of laboratory waste from the didactic chemistry laboratories, since it was possible to mitigate the generated waste, separation and correct collection. However, there are still many actions to be taken such as the waste inventory of all laboratories on both UNIFEI campuses, the creation of a more effective risk and waste management program for all research and teaching laboratories, the standardization of labeling of waste, as well as the creation of a site that guides the entire UNIFEI community for the proper disposal of laboratory waste.